ANALYSIS OF THE IMPLEMENTATION OF THE FEDERAL ASSURANCE PROGRAM OF SUPPORTING BENEFICIARIES WITH INDISPENSABLE MEDICINAL PREPARATIONS IN THE SUBJECTS OF THE RUSSIAN FEDERATION - I. K. Petrukhina; R. I. Yagudina; T. K. Ryazanova; V. A. Kurkin; S. V. Pervushkin; A. V. Egorova; L. V. Loginova; A. I. Khusainova; P. R. Blinkova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the research was to study the main indicative indicators of the implementation of The Federal Program "Provision of Essential Medicines" in 20 constituent entities of the Russian Federation based on the results of 2018 and 2019.Materials and methods. The analyzed data were provided on the basis of the request cards specially designed by the health authorities of 20 subjects of the Russian Federation located in seven federal districts.Results. It has been established that the funds allocated to the constituent entities of the Russian Federation, directly depend on the number of beneficiaries who retained the right to receive state social assistance in the form of a set of social services. These funds also correlate with the indicator "Population of the subject of the Russian Federation". In all the studied constituent entities of the Russian Federation, more than 50% of the total number of people who retained the right to preferential drug provision in 2018-2019, asked for medical help as part of the program "Provision of Essential Medicines". Herein, in the constituent entities of the Russian Federation, the average cost of one prescription amounted to 1,107.2 rubles in 2018 and 1,297.2 rubles in 2019. The estimated indicator "The average actual expenditures per 1 citizen entitled to state social assistance in the form of a set of social services, amounted to 1,723.0±90.2 rubles in 2018 and 1,526.8±80.5 rubles in 2019, which is higher than the approved input normative (823.3 rubles and 861.8 rubles in 2018 and 2019, respectively).Conclusion. Thus, an excess of average actual expenditures per citizen entitled to state social assistance in the form of a set of social services, was notified over the standards established by the decrees of the Government of the Russian Federation. The revealed discrepancy between the normative and actual expenditures can also be an indirect confirmation of the fact that the most needy beneficiaries with chronic diseases remained in the program "Provision of Essential Medicines".